Akonta: Examining the epistemology and ontology of Made in Africa Evaluation - Mjiba Frehiwot (African Evaluation Journal, 2022)
This article interrogates the epistemology and ontology of Made in Africa evaluation (MAE). Since the initial conversations about MAE as a method and theory in 2007, its importance has continued to gain traction and occupy space as a viable alternative to  strictly using evaluative tools developed outside of Africa.  The epistemology and ontology of MAE are rarely a part of discussions, debates and research, these are regarded as auxiliary to internationally recognised methods and theories. The ability of MAE to be imagined by evaluators, academics and the community strengthens its ability to operate in multiple communities across Global Africa
This article interrogates the epistemology and ontology of Made in Africa evaluation (MAE). Since the initial conversations about MAE as a method and theory in 2007, its importance has continued to gain traction and occupy space as a viable alternative to  strictly using evaluative tools developed outside of Africa.  The epistemology and ontology of MAE are rarely a part of discussions, debatesand research, these are regarded as auxiliary to internationally recognised methodsandtheories. The ability of MAE to be imagined by evaluators, academics and thecommunity strengthens its ability to operate in multiple communities across GlobalAfrica